Universal Screening and Education: A Client-Centered Protocol for Normalizing Intimate Partner Violence Conversation in Clinical Practice. Issue 4 (1st October 2020) - Todahl, Jeff; Nekkanti, Akhila; Schnabler, Simone
Abstract: Researchers, therapists, and advocates have examined the advantages and disadvantages of intimate partner violence (IPV) universal screening in health care settings. This article describes the IPV Screen and Assessment Tier (IPV-SAT), a model that adapts findings from the screening research literature for therapists and recommends IPV universal education. IPV-SAT is a framework and decision-making protocol for conducting an IPV screen, IPV education, IPV assessment, and IPV danger assessment. The article includes recommendations for IPV universal education and principles for responding to disclosures of violence. Important considerations for creating a safe context for screening and assessment and strategies for handling confidentiality are outlined. IPV education resources and recommendations are provided, along with materials to assist therapists and other health care providers to effectively assess for IPV.